Exposição acessível on-line com sistemas de gestão de conteúdo: Museu de Artes e Ofícios como estudo de caso - Marília Rodrigues Alves de Souza (2022)
This dissertation used the Case Study as a methodology, has as its central theme accessibility for people with visual impairments at the Museu de Artes e Ofícios, having been made an accessible online exhibition with content management systems as an educational resource. For the development of the work, a research was done about inclusion in museums, types of disability, accessibility and legislation. The Museu de Artes e Ofícios, its educational practices and its relations with museum education were detailed in this dissertation. The exhibition was developed on WordPress software, using Tainacan plugins and themes and One Click Acessibility plugin. The Dublin Core metadata scheme was also used to produce the catalog sheet. The acessibility of the collection was evaluated using the tools ASES - Avaliador e Simulador de Acessibilidade em Sítios and AcessMonitor. The percentage in the ASES was 80.55%, being in the third level (>=70% and 85% of the score) and the website accessibility score in the AcessMonitor was 5.9 (scale from 0 to 10). The exhibition remains online, constantly improving its accessibility and serving as a reference and inspiration for other museums guided by inclusive management of their collections on the Web.